Density profile of dark matter haloes and galaxies in the Horizon-AGN simulation: the impact of AGN feedback - Peirani, S; Dubois, Y; Volonteri, M; Devriendt, J; Bundy, K; Silk, J; Pichon, C; Kaviraj, S; Gavazzi, R; Habouzit, M (Oxford University Press, 2017)
Using a suite of three large cosmological hydrodynamical simulations, HORIZON-AGN, HORIZON-NOAGN (no AGN feedback) and HORIZON-DM (no baryons), we investigate how a typical sub-grid model for AGN feedback affects the evolution of the inner density profiles of massive dark matter haloes and galaxies. Based on direct object-to-object comparisons, we find that the integrated inner mass and density slope differences between objects formed in these three simulations (hereafter, HAGN, HnoAGN and HDM) significantly evolve with time. More specifically, at high redshift (z ~ 5), the mean central density profiles of HAGN and HnoAGN dark matter haloes tend to be much steeper than their HDM counterparts owing to the rapidly growing baryonic component and ensuing adiabatic contraction. By z ~ 1.5, these mean halo density profiles in HAGN have flattened, pummelled by powerful AGN activity (“quasarmode”): the integrated innermass difference gapswith HnoAGN haloes have widened, and those with HDM haloes have narrowed. Fast forward 9.5 billion years, down to z = 0, and the trend reverses: HAGN halo mean density profiles drift back to a more cusped shape as AGN feedback efficiency dwindles (“radio mode”), and the gaps in integrated central mass difference with HnoAGN and HDM close and broaden respectively.On the galaxy side, the story differs noticeably.Averaged stellar profile central densities and inner slopes are monotonically reduced by AGN activity as a function of cosmic time, resulting in better agreement with local observations. As both dark matter and stellar inner density profiles respond quite sensitively to the presence of a central AGN, there is hope that future observational determinations of these quantities can be used constrain AGN feedback models.